The in vitro antimicrobial evaluation of commercial essential oils and their combinations against acne. (7th June 2018) - Orchard, A.; van Vuuren, S. F.; Viljoen, A.M; Kamatou, G.
Abstract: Objective: The study investigated the efficacy of commercial essential oil combinations against the two pathogens responsible for acne with the aim to identify synergy and favourable oils to possibly use in a blend. Materials and Methods: Antimicrobial activity was assessed using the minimum inhibitory concentration (MIC) assay against Staphylococcus epidermidis (ATCC 2223) and Propionibacterium acnes (ATCC 11827), and the fractional inhibitory concentration index (ΣFIC) was calculated. Combinations displaying synergistic interactions were further investigated at varied ratios and the results plotted on isobolograms. Results: From the 408 combinations investigated, 167 combinations were identified as displaying noteworthy antimicrobial activity (MIC value ≤1.00 mg mL −1 ). Thirteen synergistic interactions were observed against S. epidermidis, and three synergistic combinations were observed against P. acnes . It was found that not one of the synergistic interactions identified were based on the combinations recommended in the layman's aroma‐therapeutic literature. Synergy was evident rather from leads based on antimicrobial activity from previous studies, thus emphasizing the importance of scientific validation. Leptospermum scoparium J.R.Forst. and G.Forst (manuka) was the essential oil mostly involved in synergistic interactions (four) against S. epidermidis . Cananga odorata (Lam.) Hook.f. and Thomson (ylang ylang) essential oil was also frequently involved in synergy where synergistic interactions could be observed against both pathogens. The combination with the lowest MIC value against both acne pathogens was Vetiveria zizanioides Stapf (vetiver) with Cinnamomum verum J.Presl (cinnamon bark) (MIC values 0.19–0.25 mg mL −1 ). Pogostemon patchouli Benth. (patchouli), V. zizanioides, C. verum and Santalum spp. (sandalwood) could be identified as the oils that contributed the most noteworthy antimicrobial activity towards the combinations. The different chemotypes of the essential oils used in the combinations predominantly resulted in similar antimicrobial activity. Conclusions: The investigated essential oil combinations resulted in at least 50% of the combinations displaying noteworthy antimicrobial activity. Most of the synergistic interactions do not necessarily correspond to the recommended layman's aroma‐therapeutic literature, which highlights a need for scientific validation of essential oil antimicrobial activity. No antagonism was observed. Abstract : The study investigated the efficacy of commercial essential oil combinations against the two pathogens responsible for acne with the aim to identify synergy and favourable oils to possibly use in a blend. No pattern could be identified for either oil contributing more towards synergy against Staphylococcus epidermidis and most of the interactions irrespective of the ratio are synergistic.